EFFECT OF MOTIVATION AND DISCIPLINE ON EMPLOYEES PERFORMANCE OF PT. CIPTA CATUR MAHKOTA - wahyu arif sujatmiko; Realize Realize (Jurnal Apresiasi Ekonomi, 2018)
PT Cipta Catur Mahkota is a sub company from PT Cipta Group. This company start their progress as a general contractor and then lately has become developer company. Now the employee are not only work based on job description, but the employee need to able generate creative and innovative ideas for the development of the organization. It takes the role of active managers in leading, organizing activities and keeping the organization’s environment. Manager must also be able to instil confidence in all members of the organization that they can work together as a synergy in order achieving maximum results. This study aims to describe how the influence of motivation and work discipline on employee performance at PT Cipta Catur Mahkota partially or simultaneously. The object of this research is field employees at PT Cipta Catur Mahkota. Which amounted to 121 respondents, with motivation (X1) and work discipline (X2). Data analysis method used is multiple linear regression analysis, which aims to know the corelation between two variables. Hypothesis testing is done by T Test, F Test and test coefficient of determination ( . Analyzing data using statistical data processing software that is SPSS version 22. The result of this study indicate that motivation has a positive and significant effect on employee performance of PT Cipta Catur Mahkota, work discipline have an effect on to positive and significant to employees performance of PT Cipta Catur Mahkota. The coefficient of determination has a value of 0.753 or 75.3%. This means that motivation variabel and work discipline has an effect through performance which amount is 75.3%.